FRC-TOuNN: Topology Optimization of Continuous Fiber Reinforced Composites using Neural Network. (March 2023) - Chandrasekhar, Aaditya; Mirzendehdel, Amir; Behandish, Morad; Suresh, Krishnan
Abstract: In this paper, we present a topology optimization (TO) framework to simultaneously optimize the matrix topology and fiber distribution of functionally graded continuous fiber-reinforced composites (FRC). Current approaches in density-based TO for FRC use the underlying finite element mesh both for analysis and design representation. This poses several limitations while enforcing sub-element fiber spacing and generating high-resolution continuous fibers. In contrast, we propose a mesh-independent representation based on a neural network (NN) both to capture the matrix topology and fiber distribution. The implicit NN-based representation enables geometric and material queries at a higher resolution than a mesh discretization. This leads to the accurate extraction of functionally-graded continuous fibers. Further, by integrating the finite element simulations into the NN computational framework, we can leverage automatic differentiation for end-to-end automated sensitivity analysis, i.e., we no longer need to manually derive cumbersome sensitivity expressions. We demonstrate the effectiveness and computational efficiency of the proposed method through several numerical examples involving various objective functions. We also show that the optimized continuous fiber reinforced composites can be directly fabricated at high resolution using additive manufacturing. Highlights: A neural network-based topology optimization method for simultaneous optimization of the matrix topology and fiber distribution and orientation of functionally graded continuous fiber-reinforced composites (FRC). Uses the NN's activation functions to span the unknown topology; the weights and bias of the NN serve as the design variables. Finite element simulations is integrated into the NN computational framework for end-to-end automated sensitivity analysis.